Cultural Diversity Competencies in Child and Youth Care Services in Portugal: Development of two measures and a brief training program. - Moleiro, C.; Marques, S.; Pacheco, P. (Children and Youth Services Review, 2011)
Few researchers have examined the training of child care workers in cultural diversity competencies, despite the growing number of ethnic minority children and youth in residential care. The present paper reports two studies. In study 1, we aimed to adapt and develop two measures of cultural diversity competencies—a self-report questionnaire and an objective measure based on a case vignette (n = 51). In study 2, we proposed a brief training program. A quasi-experimental design (n = 30) was used, with cultural competencies being evaluated before and after the training. Results revealed that (1) child care workers tended to over-estimate their self-perceived competence and that (2) the experimental group was more capable of including cultural elements in their definition of strategies and relational aspects of intervention after a brief training than the group that received no training (control). Implications of this study are discussed for further development of cultural diversity competencies in professionals working in residential child care.